KAJIAN PERUBAHAN KETERSEDIAAN RUANG TERBUKA HIJAU DI KECAMATAN TEMBALANG, KOTA SEMARANG, BERBASIS INTERPRETASI CITRA SATELIT - Riyan Nugraha; Sri Rahayu (Geoplanning: Journal of Geomatics and Planning, 2014)
The increasing population of Tembalang District (Kecamatan), Semarang, during 1991-2010 has implied in the increase of built-up areas for settlement and infrastructure that in turn reduced the green space. Tembalang District needs special attention, especially in the provision of green space because it is one of the fast developing areas in Semarang City. So, the research question is: “How has the change been in the availability of green space in Tembalang District? This study assesses the change during the period of 12 years, i.e., from 1999 to 2011. This study uses remote sensing techniques by performing image interpretation using ArcGIS 9.3 software and data satellite imagery of Tembalang in 1999 and Ikonos Satellite Imagery of it in 2011. The results show that the area of ​​green space in Tembalang was 3,214.86 Ha in 1999 and 3,017.73 Ha in 2011. The decrease during that period is 197.13 Ha. Among the recommendations of this study is the need to control the development activities to comply with the land use plan mandated by the RDTRK (Detail Spatial Plan) of Semarang to maintain the availability of green space.